Immediate consecutive microvascular decompression for bilateral classical trigeminal neuralgia - Segura-Lozano, Mauro Alberto; del Real-Gallegos, Mario Alexis; Mendoza-Lemus, Pedro; Carranza-Rentería, Octavio; Torres-Torres, Yael Rodrigo; González-Silva, Alejandro; Santoyo-Pantoja, Arturo; Munguía-Rodríguez, Aarón Giovanni (Frontiers in Neurology, 2024)
BackgroundClassical trigeminal neuralgia (TN) is characterized by sudden, severe facial pain, typically resulting from a neurovascular conflict affecting the trigeminal nerve. In rare cases, both nerves are affected simultaneously causing bilateral TN (BTN), increasing the complexity of the treatment. Microvascular decompression (MVD) is a well-established treatment for TN; however, the experience with immediate consecutive bilateral MVD procedures is limited and requires further evaluation.ObjectiveTo evaluate the safety and efficacy of immediate consecutive bilateral MVD in patients with severe BTN compared to non-consecutive bilateral MVD procedures.MethodsA retrospective analysis was conducted on 15 patients with BTN who underwent bilateral MVD. The data on clinical presentation, surgical technique, perioperative findings, complications, and follow-up outcomes of three cases of BTN treated with consecutive bilateral MVD surgeries were analyzed and compared to 12 who received separated procedures. Moreover, a detailed presentation of the three cases of consecutive MVD is provided to illustrate clinical decision-making, surgical nuances, and individual outcomes.ResultsBoth groups achieved significant pain relief (p < 0.001) without notable differences in Barrow Neurological Institute (BNI) pain intensity score (p = 0.305), indicating that both approaches were equally effective. The consecutive MVD group experienced a shorter total surgical duration (p = 0.025), while postoperative complications were comparable (p = 0.077), mostly transient with no major adverse events or mortality. At the last follow-up, the patients remained pain-free without recurrence of TN symptoms.ConclusionConsecutive bilateral MVD is a safe and effective option, comparable to non-consecutive procedures for treating BTN. This approach provides a viable alternative for patients with severe bilateral symptoms or when medical constraints limit the possibility of two separate surgeries. Further studies with larger cohorts and extended follow-up periods are needed to support these results.